Double-strand break repair and colorectal cancer: gene variants within 3' UTRs and microRNAs binding as modulators of cancer risk and clinical outcome - Naccarati, Alessio; Rosa, Fabio; Vymetalkova, Veronika; Barone, Elisa; Jiraskova, Katerina; Di Gaetano, Cornelia; Novotny, Jan; Levy, Miroslav; Vodickova, Ludmila; Gemignani, Federica; Buchler, Tomas; Landi, Stefano; et al. (Oncotarget, 2016)
Genetic variations in 3' untranslated regions of target genes may affect microRNA binding, resulting in differential protein expression. microRNAs regulate DNA repair, and single-nucleotide polymorphisms in miRNA binding sites (miRSNPs) may account for interindividual differences in the DNA repair capacity. Our hypothesis is that miRSNPs in relevant DNA repair genes may ultimately affect cancer susceptibility and impact prognosis.In the present study, we analysed the association of polymorphisms in predicted microRNA target sites of double-strand breaks (DSBs) repair genes with colorectal cancer (CRC) risk and clinical outcome. Twenty-one miRSNPs in non-homologous end-joining and homologous recombination pathways were assessed in 1111 cases and 1469 controls. The variant CC genotype of rs2155209 in MRE11A was strongly associated with decreased cancer risk when compared with the other genotypes (OR 0.54, 95% CI 0.38-0.76, p = 0.0004). A reduced expression of the reporter gene was observed for the C allele of this polymorphism by in vitro assay, suggesting a more efficient interaction with potentially binding miRNAs. In colon cancer patients, the rs2155209 CC genotype was associated with shorter survival while the TT genotype of RAD52 rs11226 with longer survival when both compared with their respective more frequent genotypes (HR 1.63, 95% CI 1.06-2.51, p = 0.03 HR 0.60, 95% CI 0.41-0.89, p = 0.01, respectively).miRSNPs in DSB repair genes involved in the maintenance of genomic stability may have a role on CRC susceptibility and clinical outcome.
Keywords: Young Adult; Male; MicroRNAs; Rad52 DNA Repair and Recombination Protein; kolorektální nádory; Genetic Predisposition to Disease; vazebná místa; MRE11 Homologue Protein; Survival Rate; DNA opravný a rekombinační protein Rad52; Genotype; mladý dospělý; následné studie; prognóza; mikro RNA; Adult; MRE11A; 3′UTR polymorphisms; double-strand break repair (DSBR) genes; Aged; dospělí; 3' nepřekládaná oblast; mužské pohlaví; senioři; jednonukleotidový polymorfismus; Case-Control Studies; colorectal cancer risk and clinical outcomes; Follow-Up Studies; DNA Repair; oprava DNA; Binding Sites; senioři nad 80 let; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; Biomarkers, Tumor; Humans; Aged, 80 and over; 3' Untranslated Regions; Colorectal Neoplasms; Prognosis; genotyp; miRNA binding sites; Female; homologní protein MRE11; lidé středního věku; nádorové biomarkery; genetická predispozice k nemoci; míra přežití; Middle Aged